Fulminating deep tissue space infection with Streptococcus constellatus presenting initially as a sore throat. Issue 3 (31st March 2020) - Glover, Joe; Kovacevic, Gorana; Walton, Gary; Parr, David
Abstract : Management of sore throat requires robust decision-making to balance successfully the conflicting risks of unnecessary antibiotic use against those of untreated bacterial infection. We present a case of fulminant sepsis caused by Streptococcus constellatus, presenting as a sore throat, initially managed conservatively. Despite subsequent appropriate anti-microbial therapy and surgical drainage, contiguous spread ultimately involved the deep neck spaces, mediastinum and thoracic wall, and was complicated by severe aspiration pneumonia, pharyngocutaneous and bronchopleural fistulation. The complexity and widespread extent of the infected spaces, in conjunction with the catabolic response to sepsis, created a life-threatening situation. Surgical closure of the pharyngeal defect, using a pectoralis-major pedicle flap, was successfully undertaken to ensure source control of the infection and heralded a complete recovery. We describe our management of this case, discuss the current approach to the management of patients presenting with a sore throat, and review the literature on S. constellatus infections.